X-ray tomography in micro-gravity - Torres Menendez, Harol; Heckel, Michael; Sack, Achim; Pöschel, Thorsten (Review of Scientific Instruments, 2019)
We present an X-ray device for use under conditions of weightlessness to produce high-speed radiograms and tomograms. The device is equipped with two detectors of different resolutions, a high temporal resolution-small area detector (4 Mpix within 13 × 13 mm2) and a low temporal resolution-large area detector (3 Mpix within 145 × 115 mm2). Using the high temporal resolution detector, the device achieves a recording rate of up to 25 655 radiograms per second, while using a low temporal resolution detector, up to 86 radiograms can be recorded per second. For the first time, we could record complete X-ray tomograms in microgravity aboard a parabolic flight in 16 s using a laboratory microfocus X-ray source. We demonstrate the operation of the device by analyzing the three-dimensional packing of particles (tomograms) and structure formation in a granular gas under periodic excitation (radiograms).
CRIS-Team Scopus Importer:2019-10-22